Recent update of mysid (Mysida) species composition in the Dnieper Reservoir, South-Eastern Ukraine, a source of several crustacean invaders to European waters - Arbaиiauskas, Ккstutis; Арбачаускас, Кестутіс; Sidagytė, Eglė; Шидагіте, Егле; Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; et al. (Regional Euro-Asian Biological Invasions Centre, 2016)
The Dnieper Reservoir has significantly contributed as a primary source of invasive Ponto-Caspian crustaceans of Europe; therefore, the mysid populations it sustains are central to the research of invasion histories. However, the reservoir remains a waterbody susceptible to changes including the advent of new species. Mysid investigations in 2012–2014 revealed five species, Limnomysis benedeni, Paramysis lacustris, P. intermedia, P. bakuensis and Katamysis warpachowskyi, inhabiting the Dnieper Reservoir, and one species, L. benedeni, known to occur in the DnieperDonbass Canal. Including the previously reported Hemimysis anomala, the currently known mysid fauna of the Dnieper Reservoir consists of six species. Two of the species, P. intermedia and P. bakuensis, are reported from the reservoir for the first time. Currently, the dominant species in the shallow littoral zone are L. benedeni and P. intermedia, while P. lacustris mostly occurs in offshore depths. Two out of six occurring species, L. benedeni and P. lacustris, were deliberately introduced into the middle reaches of the Dnieper River, which must have contributed to their establishment in the reservoir. Meanwhile most of remaining four species, presumably, have invaded the Dnieper Reservoir by shipping. However, possibilities of an accidental introduction of these species or their historical presence in some habitats of the middle reaches of the Dnieper River may not be excluded. In conclusion, there have been rather significant changes in documented species composition of mysids in the reservoir, altering the scientifically valuable source populations of European invasions. Дніпровське водосховище значно сприяло інвазіям як первинне джерело інвазійних понто-каспійських ракоподібних Европи. Таким чином, популяції мізид, які воно підтримує, є центральними у дослідженні історії інвазій. Проте водоймище залишається водним середовищем, яке змінюється, включаючи появу нових видів. У дослідженні Mysid в 2012–2014 рр. виявлено п'ять видів: Limnomysis benedeni, Paramysis lacustris, P. intermedia, P. bakuensis і Katamysis warpachowski, які мешкають у Дніпровському водосховищі, а також один вид L. benedeni, який відомий для фауни каналу «Дніпро–Донбас». Включаючи раніше зареєстровану мізиду аномаліа Гемімізис, нині відома фауна мізид Дніпровського водосховища складається з шести видів. Два види, P. intermedia і P. bakuensis, знайдені для водоймища вперше. На сьогодні домінуючими видами в мілководній літоральної зоні є L. benedeni і P. intermedia, тоді як P. lacustris в основному зустрічається на глибинах. Два з шести видів, L. benedeni та P. lacustris, навмисно інтродуковані на середній течії Дніпра, що, вірогідно, сприяло їх появі по всій водоймі. Тим часом інші чотири види, імовірно, проникли в Дніпровське водосховище шляхом вселення. Проте не можна виключати можливості випадкового розселення цих видів або їх історичної присутності у деяких середовищах мешкання на середній течії Дніпра. Авторами внесені досить значні зміни у задокументований видовий склад мізид у водоймищі.
Останнє оновлення складу мізид (Musidae) у Дніпровському водосховищі, Південно-Східна Україна, - джерелі кількох ракоподібних інвайдерів до європейських вод
Keywords: mysids of Dnieper; Мізиди Дніпра; Ponto-Caspian peracaridans; Понто-Каспійські ракоподібні; artificial water bodies; штучні водойми; invasion history; історія інвазій